Examining The Impact of Various Factors on Working From Home - Nugroho, Muhammad Fajar (Journal of Governance and Public Policy, 2024)
The COVID-19 pandemic has brought about unprecedented challenges, prompting governments worldwide to implement social distancing measures to curb the spread of the virus. As a response, many organizations, including government agencies, have adopted remote work policies, such as working from home (WFH), to ensure the continuity of their operations while safeguarding the health and safety of their employees. The Regional Development Planning Agency of Gunungkidul District is no exception, facing the need to implement WFH measures amidst the pandemic. However, transitioning to remote work presents various challenges, particularly in ensuring the effectiveness and sustainability of public services. Therefore, understanding the factors that influence the successful implementation of WFH in this context is crucial for maintaining the quality and efficiency of public services. This study focuses on identifying these factors by examining six key variables: the availability of computers and internet networks, the ability to master technology and information, HR governance rules, organizational culture, performance evaluation instruments, and the physical conditions of the working environment. These variables were chosen based on their potential impact on WFH within the Regional Development Planning Agency. By utilizing the structural equation modeling method with the partial least squares (PLS) technique, this study aims to analyze the relationships between these variables and their effects on WFH implementation. The survey conducted with all staff of Bapeda Gunungkidul District provides valuable insights into how these factors interact and influence the successful adoption of remote work practices. The results of this study highlight the significant influence of computer and internet network availability on WFH implementation, as evidenced by the path coefficient value of 0.632, the T statistic value of 4.201, and the V value of 0.000. This finding underscores the importance of adequate technological infrastructure in facilitating remote work and ensuring the continuity of public services during challenging times like the COVID-19 pandemic. This study sheds light on the critical factors that impact the successful implementation of WFH in the Regional Development Planning Agency of Gunungkidul District. By understanding these factors, HR management can better navigate the challenges of remote work and develop strategies to optimize WFH practices, thereby maintaining the delivery of essential public services amidst crises.